2022
DOI: 10.52643/jbik.v12i2.2099
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Komunikasi Terapeutik Dengan Penerapan Komunikasi Terapeutik Oleh Mahasiswa Keperawatan STIKes Medistra Indonesia Tahun 2021

Abstract: Pendekatan yang direncanakan secara sadar dimana memiliki tujuan yang berorientasi pada klien merupakan proses yang digunakan oleh perawat melalui komunikasi terapeutik. Adanya suatu komunikasi dalam keperawatan dapat meminimalisir terjadinya kesalahan ataupun kesalahpahaman dalam proses keperawatan. Dalam pelayanan kesehatan, masih terdapat perawat yang belum maksimal atau bahkan tidak menerapkan komunikasi terapeutik. Penerapan komunikasi terapeutik perlu didasari dengan pengetahuan komunikasi terapeutik ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…In contrast to research, it shows that 53% of respondents have good knowledge of therapeutic communication, 100% of respondents have good knowledge of the basics and goals of therapeutic communication, 80% of respondents have good knowledge of the stages of therapeutic communication, and 56% of respondents have good knowledge of the therapeutic communication techniques respondents are nurses at the Roemani Muhammadiyah Hospital in Semarang. Meanwhile, research showed that of the 50 respondents there were 28 (56%) nurses who had good knowledge, and 22 (44%) nurses had sufficient knowledge (Simamora et al, 2022;Tamonob et al, 2023). The majority of nursing students have good knowledge about therapeutic communication as many as 28 respondents or around 70%, for attitudes in communication the majority have good attitudes as many as 34 respondents or around 85%, and actions in therapeutic communication as perfect respondents as many as 29 respondents or around 72%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to research, it shows that 53% of respondents have good knowledge of therapeutic communication, 100% of respondents have good knowledge of the basics and goals of therapeutic communication, 80% of respondents have good knowledge of the stages of therapeutic communication, and 56% of respondents have good knowledge of the therapeutic communication techniques respondents are nurses at the Roemani Muhammadiyah Hospital in Semarang. Meanwhile, research showed that of the 50 respondents there were 28 (56%) nurses who had good knowledge, and 22 (44%) nurses had sufficient knowledge (Simamora et al, 2022;Tamonob et al, 2023). The majority of nursing students have good knowledge about therapeutic communication as many as 28 respondents or around 70%, for attitudes in communication the majority have good attitudes as many as 34 respondents or around 85%, and actions in therapeutic communication as perfect respondents as many as 29 respondents or around 72%.…”
Section: Discussionmentioning
confidence: 99%
“…Komunikasi merupakan jati diri pada manusia karena melalui komunikasi manusia dapat menjadi cerminan bagi manusia yang merupakan bagian dari masyarakat sosial serta melalui komunikasi manusia dapat saling bertukar informasi [5]. Dalam komunikasi tidak hanya sebagai sarana bersosialisasi, tetapi dalam komunikasi juga penting untuk mencapai keberhasilan terapi yang dilakukan oleh tenaga kesehatan.…”
Section: Pendahuluanunclassified